2016
DOI: 10.1002/pip.2815
|View full text |Cite
|
Sign up to set email alerts
|

Capping vertically aligned InGaAs/GaAs(Sb) quantum dots with a AlGaAsSb spacer layer in intermediate‐band solar cell devices

Abstract: This study demonstrated the feasibility of fabricating a highly stacked vertically aligned InGaAs/GaAs(Sb) quantum dot (QD) structure with an AlGaAsSb spacer layer for improving the device performance of QD intermediate-band solar cell (QD-IBSC) devices. The power-dependent photoluminescence measurements of the proposed structure revealed a blueshift in the QD ground-state emissions when the excitation power was increased, indicating the formation of an intermediate band inside the QD structure. Capping the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Also, AlAs CL prevents in segregation and In-Ga intermixing, and reduces QDs decomposition [ 54 , 55 ]. In addition to AlAs, the CLs commonly used include InGaAs, InAlGaAs, AlGaAsSb and so on, and different CLs have different effects [ 56 58 ]. Wei-Sheng Liu et al fabricated an InGaAs/GaAs(Sb) QDs with AlGaAsSb CL.…”
Section: Research Progress Of In(ga)as/gaas Qd-ibscmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, AlAs CL prevents in segregation and In-Ga intermixing, and reduces QDs decomposition [ 54 , 55 ]. In addition to AlAs, the CLs commonly used include InGaAs, InAlGaAs, AlGaAsSb and so on, and different CLs have different effects [ 56 58 ]. Wei-Sheng Liu et al fabricated an InGaAs/GaAs(Sb) QDs with AlGaAsSb CL.…”
Section: Research Progress Of In(ga)as/gaas Qd-ibscmentioning
confidence: 99%
“…Wei-Sheng Liu et al fabricated an InGaAs/GaAs(Sb) QDs with AlGaAsSb CL. It showed an enlarged band gap with the inserting of AlGaAsSb CL and the V oc is increased from 0.67 to 0.7 V [ 58 ]. T. Sugaya et al found that the In 0.2 Ga 0.8 As CLs on In 0.4 Ga 0.6 As QD solar cells could reduce the strain around the QDs and 50-stack InGaAs QDs can be grown without defects.…”
Section: Research Progress Of In(ga)as/gaas Qd-ibscmentioning
confidence: 99%
“…Vertically aligned QD structures with reduced spacer layer thickness have been observed to present several challenges that need to be overcome, such as dot-size uniformity, the formation of nonradiative recombination centers resulting from the epitaxial defects, low V oc , and the low optoelectronic conversion efficiency of the InAs/GaAs QD-IBSCs. , Due to the reduced GaAs spacer layer thickness in a multistack InAs/GaAs QD structure for electronic state coupling, the increased structural compressive strain can generate crystal dislocations, reducing the carrier lifetime and worsening the device characteristics of the QD-IBSCs.…”
mentioning
confidence: 99%
“…The increased density of dislocations in multistack QD structures can worsen the short-circuit current density and open-circuit voltage of the QD-IBSC . Therefore, the extended carrier lifetime in a QD array with reduced crystal defects is critical to enhance the absorption of sub-band-gap photons and the current–voltage characteristics in a QD-IBSC. ,, …”
mentioning
confidence: 99%
See 1 more Smart Citation